The interplay of personal and contextual diversity during the first year at Higher Education: Combining a quantitative and a qualitative approach - Jenert, Tobias; Brahm, Taiga (Frontline Learning Research, 2021)
Research on student transition into Higher Education (HE) has taken different theoretical perspectives. First, studies investigated personal variables such as students´ self-efficacy, emotions and motivation regarding the transition from school to HE. A second strand of research focused on contextual variables, for instance college effectiveness research. With this paper, we combine both the personal and the contextual approach. We aim to investigate the interaction between personal and contextual diversity during the transition into HE, taking into account students’ diversity in particular with regard to gender and individual characteristics, such as self-efficacy. We explored the heterogeneity in students’ personal characteristics by conducting a latent profile analysis (LPA) based on students’ intrinsic motivation, self-efficacy and anxiety before entering Higher Education. LPA resulted in three distinct profiles, with significant differences in how students perceived the first year. This finding suggests that students’ personal characteristics when entering Higher Education influence how they experience the study environment. To investigate the interplay between individual and contextual differences in more detail, we conducted a qualitative longitudinal study with 14 first-year students in parallel with the panel survey. We found that individual students react very differently to specific characteristics and events of the first-year environment. Our study adds to the growing body of research that aims to grasp the complexity of interactions between individual and contextual differences. Specifically, we illustrate how combining quantitative and qualitative methods can provide new insights into person-context interactions.